The Effect Of Profitability, Liquidity, Activity, and Leverage on Stock Prices to Independent Commissioners As Moderating Variables - Deshi Danuz, Sonia Zulfa; Sunardi, Nardi; Sahroni (Indonesian Development of Economics and Administration Journal, 2022)
This research was conducted to identify and analyze the effect of profitability, liquidity, activity, and leverage on stock prices to independent commissioners as moderating variables. This research concentrates on pharmaceutical and cosmetic companies listed on the Indonesia Stock Exchange period 2011 - 2021. The data for this research is secondary. This form of research combines the associative method and quantitative approach. The sample technique employed was purposive sampling method. The number of samples used in this research based on the criteria yielded 110 data for 10 periods using the statistical test tool Eviews 12. Panel data regression and moderated regression analysis are employed for analysis (MRA). Partial test results indicate that profitability and activity have a considerable and favorable effect on stock prices, liquidity has a big and negative impact on stock prices, Leverage has a favorable but negligible impact on stock prices, In addition, the independent board of commissioners has a minor and negative impact on stock prices. Multiple test showed that profitability, liquidity, activity, and leverage all have a substantial impact on stock prices. The moderated regression analysis (MRA) test results indicate that the independent board of commissioners functions as a moderator homologizer for the link between profitability, liquidity, activity, and leverage and stock prices.